Information Quality and Endogenous Project Outcomes - Deng, Mingcherng; Nan, Lin; Wen, Xiaoyan (Contemporary Accounting Research, 2019)
ABSTRACT In this study, we show that when a firm needs external financing, information quality has real effects via financing contracts on the firm's input to influence its operational outcome. Interestingly, we find that higher information quality decreases overall efficiency. Our analysis highlights the importance of considering the role of information quality in the presence of the firm's input decision upon financing contracts. In particular, information quality has a feedforward effect on the firm's real input decision via financing contracts, which in turn has a feedback effect on financing contracts and overall efficiency.